Molecular Data Suggest Long-Term in Situ Antarctic Persistence Within Antarctica's Most Speciose Plant Genus, Schistidium - Biersma, Elisabeth M.; Jackson, Jennifer A.; Stech, Michael; Griffiths, Howard; Linse, Katrin; Convey, Peter (Frontiers in Ecology and Evolution, 2018)
From glacial reconstructions it is clear that Antarctic terrestrial life must have been extremely limited throughout Quaternary glacial periods. In contrast, recent biological studies provide clear evidence for long-term in situ persistence throughout glacial times within most extant Antarctic faunal and several microbial groups. However, even now, the evolutionary history of the Antarctic flora - despite playing major role in Antarctic ecosystems - remains poorly studied. We assessed the diversity, richness and relative age divergences within Schistidium (Grimmiaceae, Bryophyta), the most species-rich plant genus in the Antarctic, as well as the plant genus containing most Antarctic endemic species. We applied phylogenetic and molecular dating methods based on nuclear ribosomal Internal Transcribed Spacer sequences, including all known Antarctic Schistidium species with available sample material. We additionally investigated the continent-wide genetic diversity within the most common Antarctic representative of the genus - the endemic species Schistidium antarctici - and performed preliminary phylogeographic analyses of the bipolar species Schistidium rivulare. Most previously described Antarctic Schistidium species were genetically distinct, confirming their specific status. Interspecific divergences of all species took place at least 1 Mya, suggesting a likely in situ persistence in Antarctica for (at least) all endemic Schistidium species. The widespread endemic species, Schistidium antarctici, diverged from other Antarctic congeners in the late Miocene, thereby revealing the oldest extant plant species currently known in Antarctica, and providing increasing support for the hypothesis of vegetation survival through multiple glacial periods. Within S. antarctici we identified several distinct clades dividing the eastern Antarctic Peninsula and Scotia Arc islands from the western Antarctic Peninsula and all continental locations. This suggests that the mountainous spine on the Antarctic Peninsula forms a strong barrier to gene flow in this species, while increased genetic diversity in the northern Maritime Antarctic indicates likely glacial refugia in this area. This study provides an important first step towards assessing the diversity and evolutionary history of the most speciose moss genus in the Antarctic. The multi-million year presence of several endemic species contributes to studies on their adaptive potential to survive climate change over both historical and contemporary timescales.